Pengaruh Akuntabilitas, Transparansi, Sistem Akuntansi Keuangan Desa, dan Partisipasi Masyarakat terhadap Pengelolaan Keuangan Desa: Studi Empiris pada Nagari se-Kecamatan Sungai Pagu, Solok Selatan - Fariz Muhammad Al-Hanif; Fefri Indra Arza; Rino Dwi Putra (Universitas Negeri Padang, 2026)
The purpose of this study is to examine the influence of accountability, transparency, the village financial accounting system, and community participation on village financial management (An Empirical Study on Nagari in Sungai Pagu Subdistrict). The data used in this research are primary data obtained through the distribution of questionnaires using a Likert scale. The research sample consists of 11 Nagari in Sungai Pagu Subdistrict, with a total of 150 respondents. The sampling technique used is purposive sampling, with the criteria being Nagari officials in Sungai Pagu who are directly involved in village financial management. Data were analyzed using multiple linear regression analysis. The results show that accountability has a positive effect on village financial management, transparency has a positive effect on village financial management, the village financial accounting system has no significant effect on village financial management, and community participation has a positive effect on village financial management in the 11 Nagari of Sungai Pagu Subdistrict, Solok Selatan Regency.